Penerapan Penomoran Rumah untuk Mendukung Layanan Publik di Jorong Rumah Panjang, Nagari Salayo Tanang Bukit Sileh, Kabupaten Solok - Ekawati, Putri Ningtias; Wardani, Anggita Cahya; Dakesa, Selia Okta; Rahmi, Naviga; Frinaldi, Aldri (CV. ITTC INDONESIA, 2025)
House numbering is a crucial aspect in improving the accuracy of population data and the effectiveness of public services at the local level. This article aims to describe the implementation of the house numbering system in Jorong Rumah Panjang, Nagari Salayo Tanang Bukit Sileh, as an effort to support social, health, and administrative services. Descriptive qualitative research was conducted through semi-structured interviews, field observations, and documentation, with data analysis using the interactive model by Miles and Huberman. The results show that the implementation of house numbering improves the accuracy of social assistance distribution, facilitates health visits, and supports logistical distribution. This system also strengthens spatial information systems and enhances coordination between residents and local government. In conclusion, house numbering provides a practical solution for managing population data and public services, while fostering active community participation. Further research could explore the implementation of digital technology for managing house number data.